Out of the ashes: an oral history of the provisional Irish Republican movement : (social movements vs terrorism) - White, Robert W. (Merrion Press, 2017)
Out of the Ashes is the definitive history of the Provisional Irish Republican movement, from its formation at the outset of the modern 'Troubles,' up to and after their official disarmament in 2005. Robert White, a prolific observer of the IRA and Sinn Féin's activities, has amassed an incomparable body of interview material from leading members of the organisation over a thirty-year period. In this defining study, the interviewees' perspectives provide extraordinary insights, not only into the inner workings of the paramilitary group, but also the complex motivations that provoked their violent actions, their eventual reform, and the mind-set of 'dissidents' who refused to lay down their arms. Those interviewed stem from every stage of the Provisionals' history, from founding figures such as Seán Mac Stiofáin, Ruari Ó Brádaigh, and Joe Cahill to the new generation who replaced them: Danny Morrison, Martin McGuinness, Marian Price, and Brendan Hughes, amongst others. Their oral perspectives provide completely unique insights into key moments within the movement's history, highlighting the real motives behind the violence that caused worldwide consternation. Out of the Ashes is a pioneering history that breaks new ground in defining how the Provisional Republican groups operated and survived from within their own ranks, and how they continued to act under international pressures to disband.--